Comparative Assessment of Quality Requirements for Medicinal Products Containing Diosmin - N. P. Antonova; E. P. Shefer; S. S. Prokhvatilova; N. E. Semenova; V. N. Makukhin; S. A. Kuchugurin; M. S. Zotova (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Currently, there is an increase in preand post-approval testing of medicinal products containing diosmin and hence a need to unify approaches to standardisation of this group of pharmaceuticals. Moreover, the State Pharmacopoeia of the Russian Federation lacks a monograph for these products.The aim of the study was to determine an approach to standardisation of medicinal products containing diosmin.Materials and methods: the study analysed scientific publications, as well as monographs of leading foreign pharmacopoeias. Experimental work was carried out using samples of diosmin-containing pharmaceuticals in the form of 500 and 1000 mg film-coated tablets produced by Russian and foreign manufacturers. The study involved high performance liquid chromatography with UV detection using an Agilent 1260 Infinity II liquid chromatography system with a diode array detector. The following reference standards were used: a diosmin RS, USP grade; a hesperidin CRS, Ph. Eur. Grade; and a diosmin CRS for testing chromatography system suitability for identification of impurities A, B, C, D, E, and F, Ph. Eur. grade.Results: the authors reviewed quality requirements for pharmaceutical products containing diosmin and analysed experimental data obtained during preand post-approval testing of Russian and foreign medicines. The comparison of regulatory documents for registered diosmin-containing medicinal products showed a difference in approaches to assessing the contents of related substances and active pharmaceutical ingredients. Having analysed the literature, experimental data and regulatory requirements for standardisation of diosmin-containing pharmaceuticals, the authors recommended an approach to standardisation. According to the approach, concomitant flavonoids (hesperidin, isorchoifolin, linarin, and diosmetin) contributing to the pharmacological activity of a medicinal product are specified as part of Assay, and process-related by-products (impurities A and D) are specified and evaluated as part of Related substances tests.Conclusion: the authors propose to evaluate the contents of concomitant flavonoids (hesperidin, isorchoifolin, linarin, diosmetin) under Assay and to specify impurities A and D, as well as single unidentified impurities and total amount of impurities under Related substances.